The Potency of Dry-Cooked Rice Waste and Tofu Dregs on Weight Gain and Feed Conversion in Beef Cattle - Fianti Nufinda Rachma; Sri Hidanah; Miyayu Soneta Sofyan; Boedi Setiawan (Universitas Airlangga, 2020)
Background: Animal feed is one of the main determinants of livestock production costs. Tofu dregs and dry-cooked rice waste is favoured by farmers as an additional feed for cattle because it is readily available and inexpensive. Tofu dregs and dry-cooked rice waste is considered to be able to provide adequate nutrition for cattle and is believed to be able to be a factor in increasing cattle daily body weight. The efficiency of feed use can be determined from feed conversion, namely the amount of feed consumed to achieve an increase of one kilogram of body weight. Purpose: To find out the average increase in daily body weight of beef cattle given tofu dregs and dry-cooked rice waste and how much feed conversion is produced at CV. Tunas Muda Tuban. Method: Using ten beef cattle to be weighed in the first week and the fourth week of observation. Result: Feeding tofu and karak dregs, had an average daily weight gain of 1.34 Kg/day. Conclusion: Provision of tofu and dry-cooked rice waste has a significant influence on the increase in body weight of beef cattle at CV.Tunas Muda, seen from the average daily body weight of 1.34 kg/day.